Challenges to fieldwork before 1914 and today: Adaptation, Omission, Rediscovery - Forêt, Philippe (Rachel Carson Center for Environment and Society, 2014)
John Chappell and, before him, Lord Curzon have reminded us that much can be gained from reviewing earlier writings and from listening to interruptions and silence.1 In January 2010, I discovered with amazement a wealth of unpublished observations while scrutinizing the drafts of maps made by the productive and flamboyant Dr. Sven Hedin (1865–1952). Secluded for decades in the National Archives of Sweden, Hedin’s precise information on the vegetation types, soil and water qualities, animal tracks, former shorelines, and abandoned settlements of Tibet and Xinjiang would have been valuable for the elaboration of a theory on climate change in extreme environments...
Keywords: fieldwork; adaptation; omission; rediscovery; Research Subject Categories::HUMANITIES and RELIGION::Religion/Theology::History of religion